2014
DOI: 10.1111/dech.12086
|View full text |Cite
|
Sign up to set email alerts
|

Performing Repatriation? The Role of Refugee Aid in Shaping New Beginnings in Mauritania

Abstract: Academic work on transitional justice has tended to focus on the most obvious and institutionalized sites where ideas about justice and transition are discussed or contested, such as truth commissions or international tribunals. Yet, there are many other sites where such ideas are framed, circulated or challenged, including sites outside transitional countries. Drawing on the case of Mauritania, where the repatriation of refugees has played a highly symbolic role during the latest 'democratic' transition, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As Jacobsen points out, there is a misconception held by many that refugees who went through a local integration program will not return to their home countries. However, studies have shown a contrary result, since refugees tend to choose to repatriate as normalcy and stability return to their countries (see Bahar, Özgüzel, Hauptmann, & Rapoport, 2019;Fresia, 2014;Weima, 2017).…”
Section: Results and Analysis Revitalizing The Local Integration Approachmentioning
confidence: 99%
“…As Jacobsen points out, there is a misconception held by many that refugees who went through a local integration program will not return to their home countries. However, studies have shown a contrary result, since refugees tend to choose to repatriate as normalcy and stability return to their countries (see Bahar, Özgüzel, Hauptmann, & Rapoport, 2019;Fresia, 2014;Weima, 2017).…”
Section: Results and Analysis Revitalizing The Local Integration Approachmentioning
confidence: 99%
“…(p. 482) When, or if, refugees do then decide to return home, much evidence points to the value of this being deliberative and incremental (Steputat, 2004). To minimize both the risk of returning to a country that has likely been negatively affected by conflict and economic devastation and the risk of losing one's foothold in the country of asylum, families may split, with certain members returning to the country of origin to reestablish political, personal, or professional ties for part or all of the year while other family members remain in exile (Al-Ali et al, 2001;Fresia, 2014;Muggeridge & Doná, 2006). "Revolving" return (Hansen, 2007) among these populations, whereby individuals continue to cycle between sites in exile and in the country of origin, can constitute a step towards "sustainable return" within a general pattern of continuing transnational movement (Steputat, 2004, p. 2).…”
Section: Return Repatriation and Retreat In The Era Of Stratified Cit...mentioning
confidence: 99%
“…After this came literature that challenged the exceptionalism that surrounds how return is conceptualized in refugee situations (cf. Fresia, 2014). Bakewell (2002), for example, suggests that the vocabulary of repatriation is loaded with assumptions about return and home that are premised on refugees approaching movement in much more definitive and unidirectional ways than other populations.…”
Section: Introductionmentioning
confidence: 99%